Taxing sugar-sweetened beverages to reduce consumption : ewill it be effective in Portugal? - Gomes, Andreia Filipa dos Santos (2016)
In the last few years, a growing number of individuals suffer from excess weight, obesity and related illnesses, which has compelled governments to implement measures that reduce the consumption of certain nutrients that in excess are detrimental to health. Since there is no paper that studies the potential impact that an extra levy on sugary drinks may have on the Portuguese consumption, this dissertation aims to answer this question, as well as understand the factors that influence it. To accomplish this, two regressions were performed, one for Soft Drinks and another for Juices & Nectars. The first conclusion withdrawn was that both GDP and the variable Tax, which intended to capture the effects of the VAT increase in 2012 for these drinks, were not statistically significant, for none of the two regressions. The second conclusion is that education is a significant variable for Juices & Nectars, but not for Soft drinks. The opposite is true for the variable Maximum Temperature, which shows significance for Soft Drinks and not for Juices & Nectars. In short, we can conclude that, in the Portuguese case, an extra tax does not seem to be the most appropriate tool to fight obesity and potential alternatives may be educational programs, partnerships with producers to foster reformulation of products or to focus on other nutrients that Portuguese consume more, namely fats and salt.